2003
DOI: 10.1161/01.cir.0000077912.12202.fc
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Plasma von Willebrand Factor and Soluble P-Selectin as Indices of Endothelial Damage and Platelet Activation in 994 Patients With Nonvalvular Atrial Fibrillation

Abstract: Background-Abnormal plasma markers of a prothrombotic state have been described in atrial fibrillation (AF), but no such marker has yet been shown to reliably predict future stroke or cardiovascular outcome in AF. We hypothesized that raised plasma levels of von Willebrand factor (vWf, an index of endothelial damage/dysfunction) and/or soluble P-selectin (sP-sel, an index of platelet activation) might predict vascular events in AF. Methods and Results-We measured vWf and sP-sel levels by ELISA in 994 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(49 citation statements)
references
References 29 publications
3
45
1
Order By: Relevance
“…An elevation of FVIII [18, 34] and VWF [3538] has been described earlier in the peripheral samples AF patients and it has been proposed to be attributed to endothelial damage. Moreover, elevated levels of VWF have been associated with increased stroke risk and poor prognosis [36, 39, 40]. Only few papers enrolling a limited number of patients have investigated the levels of VWF in AF patients from both intracardiac and peripheral blood samples, but in these studies FVIII levels were not determined [27, 41].…”
Section: Discussionmentioning
confidence: 99%
“…An elevation of FVIII [18, 34] and VWF [3538] has been described earlier in the peripheral samples AF patients and it has been proposed to be attributed to endothelial damage. Moreover, elevated levels of VWF have been associated with increased stroke risk and poor prognosis [36, 39, 40]. Only few papers enrolling a limited number of patients have investigated the levels of VWF in AF patients from both intracardiac and peripheral blood samples, but in these studies FVIII levels were not determined [27, 41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the event rates were similar between groups with and without atrial fibrillation for males. A possible interpretation for the gender difference in atrial fibrillation-related thromboembolism risk was that a higher von Willebrand factor level was observed in females with atrial fibrillation, but not in males with atrial fibrillation, as compared with that of non- atrial fibrillation patients 30. In a hospital-based study of 947 patients with first-ever ischemic stroke, the prevalence of atrial fibrillation was significantly higher in elderly patients aged 80 years or older (29%) than in those aged less than 80 years (11%) 31…”
Section: Risk Factorsmentioning
confidence: 99%
“…149 In multivariable Cox models, the hazard ratio for incident AF associated with a 1-standard deviation increase in VWF was 1.17 (95% CI 1.11–1.23). Conway et al 150 and Krishnamoorthy et al 151 reported that raised VWF levels in patients with AF predicted stroke and vascular events, and Roldan et al 152 found that high VWF levels are an independent risk factor for adverse events in AF patients on anticoagulant therapy. The concentrations of VWF in LA blood are increased in patients with persistent AF and are higher than in the LA of those with paroxysmal AF or controls.…”
Section: Atrial Myopathy and Stroke Riskmentioning
confidence: 99%